Didaktični pripomočki in oprema za vzgojno-izobraževalni proces otrok s posebnimi potrebami - Pšunder, Majda (Revija za elementarno izobraževanje, 2010)
In the educational process, children with special needs require a different, personalized approach and adapted teaching methods and technology. The article presents innovations and opportunities for using didactical instrumentsand equipment for children with special needs. It is extremely important to consider the wishes, demands and needs of children with special needs. It is also important to make adjustments to the learning process, teaching materials, additional training of teaching staff and the use of appropriate teaching equipment with special devices that are adapted to users with special needs. Modern didactic tools and the development of ICT (Information and Communication Technologies) enable children with special needs, at all levels of education, additional improvement and development.
Keywords: vzgoja in izobraževanje; otroci s posebnimi potrebami; didaktični pripomočki; didaktična oprema; pouk